Analysis of Regional Financial Management and the Performance of the Bogor Regency Local Government - Innayatu Robania; Yohanes Indrayono; Arief Tri Hardiyanto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze regional financial management and its correlation with the performance of the Bogor Regency Local Government, particularly in mandatory government affairs related to basic services. The background of the research is based on the phenomenon that an increase in budget realization is not always followed by an improvement in performance achievement. This study uses a descriptive approach by utilizing secondary data sourced from the Accountability Report (LKPJ) for the 2023 and 2024 Fiscal Years. Analysis was conducted on the budget absorption patterns, performance achievements of regional apparatus, and the effectiveness of regional financial management. The research results show that although the budget absorption rate is relatively high, the performance achievements among departments and regional apparatuses still vary. In addition, there was a backlog of budget realization at the end of the year, which has the potential to reduce the effectiveness of program implementation. The relationship between regional financial management and performance is not linear, where an increase in budget realization does not automatically improve performance outcomes. The more influential factors include the quality of planning, the effectiveness of implementation, as well as performance control and evaluation. Therefore, regional financial management needs to be directed toward an outcome-based approach.